Social identity and Navajo High school students is a strong social identity important in the school context? - Hinkley, John W.; Marsh, Herbert W.; McInerney, Dennis M. ([Place of publication not identified] International Association for Cross-Cultural Psychology, 2002)
In this paper, we explore the concept of identity. We do this by suggesting that one's identity self-concept is multi-dimensional (personal, social, & cultural). Before examining the question in the title, we distinguish between these constructs. We then describe social identity theory and illustrate its utility by examining Navajo high school students' positive and negative ability beliefs about school and how social identity theory might explain the results. We conclude by pointing to the need for more research in this important area of study, particularly in terms of the need for similar research with other cultural groups.
Includes bibliographical references.
Downloaded from http://scholarworks.gvsu.edu/orpc/vol3/iss1/5
Keywords: Group identity